Kirkpatrick Based Evaluation of IT-Oriented Extension to Improve Services in the PPHPM Farmers Cooperative - Arief Darmawan, Figo; Nurlaela, Siti; Yekti, Ananti (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Evaluation of extension activities is a process of assessing an extension program. Therefore, it is essential to conduct evaluations in every extension activity to determine the program's success. The purpose of this study is to measure evaluation outcomes using the Kirkpatrick method, specifically Level 1 (Reaction) and Level 2 (Learning), regarding the use of information technology to improve services in the PPHPM Cooperative in Purwobinangun Village, Pakem Sub-district, Sleman Regency. This research was conducted in April 2025 using a descriptive analysis method with evaluation questionnaires distributed to 20 PPHPM cooperative administrators. The results showed that Level 1 evaluation scored 32.3 or an average of 4.61. Level 2 evaluation, conducted through pre-tests and post-tests, indicated improvements in knowledge (0.15), attitudes (0.5), and skills (2.75). The Extension Effectiveness (EE) in improving knowledge was 1.5% (categorized as less effective), attitudes 2% (less effective), and skills 91.67% (effective). The Extension Behavior Change Effectiveness (EBCE) in the aspects of knowledge was 50% (moderately effective), attitudes 55% (moderately effective), and skills 91.67% (effective).